RARE EARTH ELEMENT PARTITIONING BETWEEN TITANITE AND SILICATE MELTS: HENRY'S LAW REVISITED - Prowatke S.; Klemme S. (My University, 2006)
We present detailed experimental results on the partitioning of rare earth elements (REE) between titanite and a range of different silicate melts. Our results show that Henry's law of trace element partitioning depends on bulk composition, the available partners for heterovalent substitution, crystal composition, and melt composition. We illustrate that the partition coefficients for Sm depend very strongly on the bulk concentration of Sm in the system. The substitution mechanism, by which rare earth elements are incorporated into the crystal structure, plays an important role for trace element partitioning and also for the onset of Henry's law. Our data show that there are clear differences between substitution mechanisms of major elements compared to elements which are present only as traces. Our experiments also clearly show that the onset of Henry's law depends on the concentrations of the sum of all trace elements which are incorporated into the crystal by the same substitution mechanism. For geochemical modelling of magmatic processes involving titanite, and indeed other accessory phases, it is of crucial importance to first evaluate whether the REE, and other trace elements, are present as traces or as major elements, only then appropriate D values may be chosen. © 2006 Elsevier Inc. All rights reserved.